2020
DOI: 10.3389/fonc.2020.572904
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Autophagy in Glioblastoma Treatment With Phosphoinositide 3-Kinase/Protein Kinase B/Mammalian Target of Rapamycin Signaling Pathway Inhibitors

Abstract: Glioblastoma (GB) is the most malignant and aggressive form of brain tumor, characterized by frequent hyperactivation of the phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) signaling pathway. PI3K/AKT/mTOR inhibitors have a promising clinical efficacy theoretically. However, strong drug resistance is developed in GB against the PI3K/AKT/mTOR inhibitors due to the cytoprotective effect and the adaptive response of autophagy during the treatment of GB. Activation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 107 publications
(141 reference statements)
0
20
0
1
Order By: Relevance
“… 19 Inhibition of the PI3K/Akt/mTOR signaling pathway has a promising clinical efficacy since activation of autophagy by the PI3K/Akt/mTOR inhibitors can enhance treatment sensitivity and trigger cell survival once drug resistance occurs in cancer cells. 37 More importantly, miR-7-5p was verified to target EGFR, which has the capability to regulate gastric cancer cell proliferation and apoptosis through regulation of downstream pathways. 18 Notably, reduction in the miR-7-5p expression contributes to the increase of EGFR expression and activation of the PI3K/AKT/c-Myc signaling pathway in the context of glioma.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Inhibition of the PI3K/Akt/mTOR signaling pathway has a promising clinical efficacy since activation of autophagy by the PI3K/Akt/mTOR inhibitors can enhance treatment sensitivity and trigger cell survival once drug resistance occurs in cancer cells. 37 More importantly, miR-7-5p was verified to target EGFR, which has the capability to regulate gastric cancer cell proliferation and apoptosis through regulation of downstream pathways. 18 Notably, reduction in the miR-7-5p expression contributes to the increase of EGFR expression and activation of the PI3K/AKT/c-Myc signaling pathway in the context of glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Rapamycin is a new macrolide antibiotic and an anti-cancer drug certified by the FDA ( 26 ). Research has shown that rapamycin can prevent or delay the occurrence of tumours, including colon cancer ( 27 ), glioblastoma ( 28 ), renal cell cancer ( 29 ), and ovarian cancer ( 30 ). At present, a rapamycin phase III clinical trial has been completed, and its safety and therapeutic effects have been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…The release of ROS could stimulate autophagy and apoptosis in the liver [9,10]. We determined Beclin-1 and LC3 as well as P62 (autophagy markers) and Bcl-2 family as well as Caspase family (apoptosis markers) by qRT PCR, WB, and immunohistochemistry [13,28]. We found that PEM injection enabled the injured liver to produce more P62 and Bcl-2 and reduce Beclin-1, LC3, Bax, Caspase 9, and Caspase 3.…”
Section: Ppar Researchmentioning
confidence: 95%